Analisis Strategi Pengembangan Profesionalisme Guru Melalui Program Komunitas Belajar (Learning Community) Di Era Transformasi Digital - Dede Irma Sitanggang; Bintang Simbolon; Erni Murniarti (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
Teacher professionalism is the primary key to improving educational output quality in the era of digital transformation. This study aims to analyze strategies for developing teacher professionalism through the strengthening of Learning Communities (Kombel) as a platform for peer collaboration and the optimization of the Platform Merdeka Mengajar (PMM). Using a descriptive qualitative approach, data were collected at TK Ecole de Smarties through participant observation, in-depth interviews with five educators (FE, FS, DE, AR, and MS), and documentary studies of teachers' digital portfolios. The evaluation focused on the extent to which reflective discussions within the Learning Community could bridge the pedagogical and technological competency gaps that have historically been difficult to address through conventional one-way training. The results indicate that development strategies based on internal school collaboration are significantly more effective in improving pedagogical competency compared to formal, centralized training. This effectiveness stems from the provision of space for teachers to engage in contextual reflective practice and provide direct peer feedback in a psychologically safe environment. Furthermore, the integration of PMM into Learning Community activities has been proven to accelerate access to relevant curriculum references, thereby creating a sustainable independent learning ecosystem. The study concludes that strengthening instructional leadership from the school principal is essential to maintaining the consistency of these communities as a driving force for teacher professionalism. Consequently, the synergy between digital tools and human interaction remains the core of modern professional development strategies.